Phototoxic effect of visible blue light on Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis in patients with chronic periodontitis (An in-vitro study) - Ali R AbdulAzeez; Maha S Mahmood; Wifaq M Ali (College of Dentistry/ University of Baghdad, 2015)
Background: The aim of this study was to determine phototoxic effect of visible blue light on anaerobic periodontal pathogens namely Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis. Materials and methods: Strains of Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis were isolated from pockets of systemically healthy patients aged between 35-55 years old with pocket depths of 5-6 mm, the bacteria cultured on special blood Agar plates solid media, then subjected to visible blue light emitted from commercially available light cure devise (LED curing light); that emits blue light (400-500nm) of 1000mw energy at different periods of time exposures, then the CFU of each plate was measured by direct colony count with the aid of open CFU software after 48hours of anaerobic incubation. Results: There was a decrease in CFU for both microorganisms as we proceeded from zero, 20, 40 and 60 seconds of blue light exposure. Conclusion: there was a phototoxic effect for the visible blue light emitted from the light curing device against the anaerobic periodontal pathogens. Key words: Blue light, CFU, anaerobic periodontal pathogen.